Hubungan Kebiasaan Merokok Dan Mengkonsumsi Kafein Dengan Kejadian Osteoporosis Pada Usia Lanjut - Dwi Nonita Nugraheni; Sri Wahyu Basuki; Anika Candrasari; Budi Hernawan (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
Osteoporosis is a disease that is classified as a silent killer because it is not detected early and only known after the fracture occurs. Smoking habits are a risk factor for osteoporosis, because smokers lose bone mass faster than nonsmokers. Excess caffeine intake is associated with the effect of caffeine on bone homeostasis. The purpose of this study was to analyze the relationship between smoking and caffeine consumption and the incidence of osteoporosis in the elderly.The design of this research is a literature study or literature review. This study draws sources from Pubmed, Science Direct, and Google Scholar with the keywords: (smoking OR smoking habits) AND (caffeine OR caffeine consumption OR drink coffee) AND (osteoporosis) AND (elderly OR aged). The search results showed 1,136 articles were found, then after the duplicates were removed the remaining 1,104 articles. Then identified based on the title, abstract, and eligibility in accordance with the restriction criteria, 8 articles were reviewed. The research results from the article stated that smoking can increase the risk of osteoporosis. High caffeine consumption can put you at risk for osteoporosis, while low to moderate caffeine consumption can lower your risk of osteoporosis. Based on the results of the research that has been done, it can be concluded that there is a significant relationship between smoking habits and high consumption of caffeine on the risk of osteoporosis in the elderly.